Measuring the Oil Risk Effect on Industry Volatility Shocks - Ben Sita, Bernard (2017)
I examine the information sequential hypothesis in complementary oil markets. Unlike the underreaction hypothesis suggested as an explanation to the lagged negative oil effect of financial return, a sequential information schedule through crude oil and gasoline provides a differential dynamic in the way oil risk is channeled to financial markets. Not only do I find that the market response to oil volatility risk is contemporaneous, but that crude oil triggers financial risk at the time of information, whereas gasoline effects of financial risk are subsequent to crude oil effects.